ANALISIS PEMBELAAN TERPAKSA DALAM TINDAK PIDANA PEMBUNUHAN YANG DILAKUKAN OLEH ANAK (Berdasarkan Putusan Nomor: 1/Pid.Sus-Anak/2020/PN Kpn) - Sonia, Shoifatus (Journal of Law and Administrative Science, 2025)
This study examines the application of law to cases of forced defense in the crime of murder committed by children based on Kepanjen District Court Decision Number 1/Pid.Sus-Anak/2020/PN Kpn. The aim is to analyze the criminalization process for child perpetrators of criminal acts and consider the legal basis used by judges in issuing decisions. This study uses a normative juridical method with a statutory and case-based approach, utilizing the Criminal Code, Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, and court decisions as the main materials. The results of the study indicate that the criminalization process for children in this case is regulated by the Juvenile Criminal Justice System Law, however, the judge's considerations did not fully consider the provisions of Article 49 paragraph (2) of the Criminal Code concerning excessive forced defense. The defendant's actions should be viewed as a form of forced defense so that they can be released from all legal charges. This finding emphasizes the importance of judges' consistency in interpreting the reasons for expungement of criminal penalties so that decisions are more just, especially for children in conflict with the law.